Leaving and Entering Religion:Understanding Religious Conversion in the Discourse of Religious Freedom and Human Right - Paais, Vikry Reinaldo (Satya Widya: Jurnal Studi Agama, 2023)
Religious conversion is a problematic phenomenon. It is supported based on religious freedom, but opposed based on religious doctrines and truth claims. The debate on religious conversion in relation to freedom of religion or belief (FoRB) tends to stop on the dichotomy of universalism and relativism of human rights. That is, religious conversion is recognized as a universal value, but in a particular context became relative. In this perspective, the implementation of religious conversion, which should be universal, becomes limited. As a result, there are various kinds of stigmatization against the subjects of religious conversion, for instance, they are labeled as "heretics", "infidels", "apostates", and even "dissidents" against religion. Therefore, to explain religious conversion in relation to religious freedom and human rights, I do not stop at the dichotomy of universalism and relativism of human rights. However, religious conversion needs to be analyzed as part of the freedom of religion whose subjects must be protected. This paper will analyze the issue of religious conversion in two perspectives: first, how religious conversion (in and out conversion) in religious doctrines and teachings; and, second, how to understand religious conversion in the discourse of freedom of religion which is closely intertwined with human rights. The method used in this paper is a combination of interviews and literature study. The findings in this research show that freedom of religion is often constrained by religion itself (so-called religious relativism)